Modeling of Drug Release Kinetics from Stimuli- Responsive Micelles and Liposomes: A review - AlSawaftah, Nour Majdi (2021)
Nanocarriers such as micelles and liposomes were developed to enhance the delivery of therapeutic drugs to tumors. Internal or external stimuli can be applied to achieve spatiotemporal controlled release from these carriers. This will result in enhancing the therapeutic efficacy of anti-neoplastic drugs while reducing their toxicity. Mathematical modeling is used to simulate drug release from nanocarriers; this will facilitate and optimize the development and design of desirable nanocarriers in a systematic manner, rather than the existing trial-and-error approach. This review summarizes nine mathematical models often used to simulate drug release from drug delivery systems and reviews studies that employed these models to simulate drug release from conventional micelles and liposomes, as well as temperature-, pH-, and ultrasound-triggered micelles and liposomes.